Hemodynamic Response to Orotracheal Intubation: Comparison between Macintosh, McCoy, and C-MAC Video Laryngoscope - Aggarwal, Hiteshi (Anesth Essays Res, 2019)
BACKGROUND: The most commonly used devices for direct visualization of the larynx and tracheal intubation are Macintosh and McCoy laryngoscopes. C-MAC video laryngoscope, based on the principles of indirect laryngoscopy, has been introduced into clinical practice in recent years. Video laryngoscope may be useful in difficult tracheal intubation situations. AIM: We aimed at comparing the McCoy and C-MAC video laryngoscope with conventional Macintosh laryngoscope for hemodynamic responses of orotracheal intubation among adults receiving general anesthesia for elective surgeries. SETTINGS AND DESIGN: This was a hospital-based randomized, double-blind, comparison, done between June 2015 and October 2016 after permission of institutional ethical committee. MATERIALS AND METHODS: One hundred and fifty patients with normal airways undergoing elective general anesthesia were randomly allocated to undergo intubation using either Macintosh (Group A), McCoy (Group B), or C-MAC video laryngoscope (Group C). Hemodynamic changes associated with intubation were recorded immediately before and after laryngoscopy and intubation, every minute for 5 min and at 10 min after intubation by an independent observer. The time taken to perform endotracheal intubation and Cormack and Lehane score were also noted in all three groups. STATISTICAL ANALYSIS: Data were compiled, and statistical analysis was performed using SPSS 17.0 version. RESULTS: Hemodynamic response after intubation was least in Group B (McCoy) as compared to Group A (Macintosh) and Group C (C-Mac) (P = 0.001). Ninety-two percentage patients were in Cormack and Lehane score Class I in Group C in comparison to 52% in Group A and 48% in Group B (P = 0.000). Time for intubation taken in Group A, Group B, and Group C was 15.53 ± 1.53 min, 18.65 ± 0.44 min, and 22.82 ± 1.323 min, respectively (P = 0.000). CONCLUSION: The McCoy laryngoscope provided better attenuation of hemodynamic responses to laryngoscopy and intubation than the Macintosh and C-Mac video laryngoscope whereas more appearance of Cormack and Lehane score Class I was seen with the C-MAC video laryngoscope. Furthermore, the time taken to perform endotracheal intubation was the longest with the C-MAC video laryngoscope.